2010
DOI: 10.5395/jkacd.2010.35.6.445
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of novel composite using Portland cement for retro-filling material

Abstract: Objectives:The aim of this study was to compare apical sealing ability and physical properties of MTA, MTA -AH-plus mixture (AMTA) and experimental Portland cement -Epoxy resin mixture (EPPC) for a development of a novel retro-filling material. Materials and Methods: Forty-nine extracted roots were instrumented and filled with gutta-percha. Apical root was resected at 3 mm and the retro-filling cavity was prepared for 3 mm depth. Roots were randomly divided into 3 groups of 15 roots each. The retro-filling was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In this respect, a short setting time in addition to biocompatibility and sealing ability is necessary for an ideal root-end filling material (17,24). The development of fast-setting MTA has been attempted by many researchers (14)(15)(16)(17)24). However, most of these approaches were based on the addition of chemical setting accelerators, some of which showed adverse physical and biological effects (1,15,16).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this respect, a short setting time in addition to biocompatibility and sealing ability is necessary for an ideal root-end filling material (17,24). The development of fast-setting MTA has been attempted by many researchers (14)(15)(16)(17)24). However, most of these approaches were based on the addition of chemical setting accelerators, some of which showed adverse physical and biological effects (1,15,16).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, Kim et al (22) reported that MTA failed to set in the presence of FBS. There also have been reports that the washout of MTA can occur when MTA is used as a retrograde filling material (13,14,22). Initial looseness of MTA, ie, it is not set or weakened physical condition, occurs in the presence of tissue fluid or blood flow and may threaten the hermetic sealing of communicating channels between the root canal system and the periradicular tissues, thereby resulting in the failure of endodontic surgery.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While some studies suggest that longer setting times might result in increased material strength and reduced solubility, prolonging the setting time for pulp capping materials may have negative consequences, such as increased chair time, patient discomfort, and higher risks of material displacement or contamination before the material has fully set [5,[39][40][41][42][43]. Notably, the chair time is an important factor for children undergoing dental treatment owing to their specific characteristics, such as shorter attention spans and a tendency to become anxious or restless.…”
Section: Discussionmentioning
confidence: 99%